Barcode sequencing identifies resistant mechanisms to epidermal growth factor receptor inhibitors in circulating tumor DNA of lung cancer patients. Issue 10 (19th August 2019) - Kitazono, Satoru; Sakai, Kazuko; Yanagitani, Noriko; Ariyasu, Ryo; Yoshizawa, Takahiro; Dotsu, Yosuke; Koyama, Junji; Saiki, Masafumi; Sonoda, Tomoaki; Nishikawa, Shingo; Uchibori, Ken; Horiike, Atsushi; et al.
Abstract: Most patients with epidermal growth factor receptor (EGFR) mutation‐positive non‐small cell lung cancer (NSCLC) will inevitably develop acquired resistance induced by treatment with EGFR tyrosine kinase inhibitors (EGFR‐TKI). The mechanisms of resistance to EGFR‐TKI are multifactorial, and the detection of these mechanisms is critical for treatment choices in patients who have progressed after EGFR‐TKI therapy. We evaluated the feasibility of a molecular barcode method using next‐generation sequencing to detect multifactorial resistance mechanisms in circulating tumor DNA and compared the results with those obtained using other technologies. Plasma samples were collected from 25 EGFR mutation‐positive NSCLC patients after the development of EGFR‐TKI resistance. Somatic mutation profiles of these samples were assessed using two methods of next‐generation sequencing and droplet digital PCR (ddPCR). The positive rate for EGFR ‐sensitizing mutations was 18/25 (72.0%) using ddPCR, 17/25 (68.0%) using amplicon sequencing, and 19/25 (76.0%) using molecular barcode sequencing. Rate of the EGFR T790M resistance mutation among patients with EGFR ‐sensitizing mutations was shown to be 7/18 (38.9%) using ddPCR, 6/17 (35.3%) using amplicon sequencing, and 8/19 (42.1%) using molecular barcode sequencing. Copy number gain in the MET gene was detected in three cases using ddPCR. PIK3CA, KRAS and TP53 mutations were detected using amplicon sequencing. Molecular barcode sequencing detected PIK3CA, TP53, KRAS, and MAP2K1 mutations. Results of the three assays were comparable; however, in cell‐free DNA, molecular barcode sequencing detected mutations causing multifactorial resistance more sensitively than did the other assays. Abstract : Molecular barcoding method using next‐generation sequencing is a suitable technology to detect multifactorial resistance mechanisms in circulating tumor DNA of EGFR mutation‐positive lung cancer patients.